PERANAN Ulva pertusa DALAM MENURUNKAN PENYERAPAN TIMBAL (PB) OLEH KERANG DARAH (Anadara granosa) DAN MENEKAN PERTUMBUHAN DINOFLAGELLATA (Noctiluca miliaris) - Moch. Amin Alamsjah (The East Java Biological Society, 2010)
Profile of shell with toxic and non-toxic are not different, whereas these toxin is caused by absorption of lead from contamination water and bioactive compound of Dinoflagellata.The other side, an active compound of Ulva pertusa polyunsaturated fatty acid which has ability to potent for survivability of Dinoflagellata (Noctiluca miliaris). U. pertusa is also known to have capability as a biosorption in the sea. The results showed that the effect of algicidal substances U. pertusa was not influence on survivability of shell however it can decrease the growth of Dinofl agellata (N. miliaris) and to absorb lead. Quantifi cation analysis of fatty acid composition also showed that U. pertusa is dominated by PUFA as much as 59% of fatty acid total and has algicidal substances of HDTA, ALA, and ODTA were 1094.44 mg/100g. Analysis of lead in shell, U. pertusa and water showed that they have a significant correlation, where U. pertusa (400 g) can absorb lead until 78.17%, which the initial concentration of lead in U. pertusa and shell were 1.09 mg/kg and less than 0.14 mg/kg, respectively.